Developing management pathways for hypertensive disorders of pregnancy (HDP) in Indonesian primary care: a study protocol - Fitriana Murriya Ekawati; Sharon Licqurish; Ova Emilia; Jane Gunn; Shaun Brennecke; Phyllis Lau (BMC, 2019)
Abstract Background National and international guidelines for the management of hypertensive disorders of pregnancy (HDP) are available in developing countries. However, more detailed clinical pathways for primary care settings are limited. This study focuses on Indonesia, where 72% of women who died from HDP and its complications had received less appropriate treatment according to international guidelines. There is an urgent need to develop primary care focused pathways that enable general practitioners (GPs), midwives and other relevant providers to manage HDP better. Objectives This paper describes a study protocol for the development of HDP management pathways for Indonesian primary care settings. Methods This study design is informed by Implementation Science theories and consists of three phases. The exploratory phase will involve conducting semi-structured interviews with key Indonesian primary care stakeholders to explore their experiences and views on HDP management. The development phase will apply evidence from the literature review and results of the exploratory phase to develop HDP management pathways contextualised to Indonesian primary care settings. Consensus will be sought from approximately 50 experts, consist of general practitioners (GPs), midwives, obstetricians, nurses and policy makers using Delphi technique survey. The evaluation phase will involve a pilot study to evaluate the pathways' acceptability and feasibility in a sample of Indonesian primary care practices using mixed methods. Discussion The implementation science frameworks inform and guide the phases in this study. Qualitative interviews in the exploratory phase are conducive to eliciting opinions from key stakeholders. Using Delphi technique at the development phase is suitable to seek participants' consensus on HDP management in primary care. Observations, focus group discussions, interviews as well as analysis of patients' medical records at the evaluation phase are expected to provide a comprehensive investigation of the implementation of the pathways in practice settings.